ESTIMATION OF THE EFFECTIVENESS OF APPLICATION OF THE COMBINED METHOD OF TREATMENT OF CHRONIC UPPERCULAR PERIODONTITIS - Kh.Kh. Khozhiev (Scholar Express Journal, 2021)
The main role in the development of apical periodontitis belongs to pathogenic microflora. The inflammatory process in the apical periodontium develops as a consequence of pulp necrosis and is caused by the intake of the infectious toxic contents of the root canals of the teeth through the apical foramen. This article presents an analysis of microbiological studies of the effectiveness of the combined method of treatment of chronic apical periodontitis by the combined use of new methods of depot and apexphoresis with the combined use of the method of fluctuorization.
Keywords: Periodontitis; Depophoresis; Microflora